2018
DOI: 10.1016/j.cherd.2018.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Gas–liquid mixing in dual agitated vessels in the heterogeneous regime

Abstract: Gas-liquid multi-phase processes are widely used for reactions such as oxidation and hydrogenation. There is a trend for such processes to increase the productivity of the reactions, one method of which is to increase the gas flow rate into the vessel. This means that it is important to understand how these reactors perform as high gas flow rates occurs well into the heterogeneous regime. This paper investigates the mixing performance for the dual axial radial agitated vessel of 0.61 m in diameter. 6 blade dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Existing measurement techniques for identifying the different regimes are multiple, including optical (Yawalkar et al 2002), level probes (Gao et al 2001), ultrasonics (Cents et al 2005) and tomography [Electrical Resistance ERT (Forte et al 2019;Jamshed et al 2018), X-ray (Ford et al 2008), γ-ray (Veera et al 2001)], but are often limited by practical considerations (invasiveness, retrofitting, opacity, safety) and cost issues. The mentioned systems all require high investment cost in terms of devices and operations.…”
Section: Sensing and Measurement Techniquesmentioning
confidence: 99%
“…Existing measurement techniques for identifying the different regimes are multiple, including optical (Yawalkar et al 2002), level probes (Gao et al 2001), ultrasonics (Cents et al 2005) and tomography [Electrical Resistance ERT (Forte et al 2019;Jamshed et al 2018), X-ray (Ford et al 2008), γ-ray (Veera et al 2001)], but are often limited by practical considerations (invasiveness, retrofitting, opacity, safety) and cost issues. The mentioned systems all require high investment cost in terms of devices and operations.…”
Section: Sensing and Measurement Techniquesmentioning
confidence: 99%
“…where σ c is the conductivity of the continuous phase and σ m is the conductivity of the biphasic mixture. An alternative approach was proposed by Montante and Paglianti 49 and applied extensively by Jamshed et al, 50 which used a dimensionless conductivity ε (ε = 100…”
Section: Ert For Gas Hold-upmentioning
confidence: 99%
“…where σ c is the conductivity of the continuous phase and σ m is the conductivity of the biphasic mixture. An alternative approach was proposed by Montante and Paglianti and applied extensively by Jamshed et al, which used a dimensionless conductivity ε ( ε = 100(1 − σ m / σ c )) proportional to the gas hold‐up to describe sparging performance of different impellers; however, the authors indicate this parameter as proportional to the gas hold‐up and not as an absolute value. Furthermore, in the investigated range of gas hold‐up (approximately 1–15%), the simplification used by Montante and Paglianti can be considered proportional (with a factor of approximately 0.7) to the Maxwell's equation.…”
Section: Theorymentioning
confidence: 99%
“…For gas-liquid mixing, for example, high mass transfer coefficients can be achieved when employing sparged agitated vessels [6]. Hence, many studies have investigated these mixing systems, especially with regard to gas dispersion in Newtonian fluids [7][8][9][10]. Although fewer studies refer to the aeration of non-Newtonian fluids, a broad range of industrial applicability can still be observed in food, chemical, biochemical, pulp and paper, and painting industries [11].…”
Section: Introductionmentioning
confidence: 99%